Imaging necrosis during treatment is associated with worse survival in EORTC 26101 study. (11th June 2019) - Nowosielski, Martha; Gorlia, Thierry; Bromberg, Jacoline E.C.; Sahm, Felix; Harting, Inga; Kickingereder, Philipp; Brandes, Alba A.; Taphoorn, Martin J.B.; Taal, Walter; Domont, Julien; Idbaih, Ahmed; Campone, Mario; et al.
Abstract : Objective: Imaging necrosis on MRI scans was assessed and compared to outcome measures of the European Organisation for Research and Treatment of Cancer 26101 phase III trial that compared single-agent lomustine with lomustine plus bevacizumab in patients with progressive glioblastoma. Methods: MRI in this post hoc analysis was available for 359 patients (lomustine = 127, lomustine + bevacizumab = 232). First, imaging necrosis at baseline being formally measurable (>10 × 10 mm, given 2 slices) was assessed. At weeks 6 and 12 of treatment, it was analyzed whether this necrosis remained stable or increased >25% calculated by 2 perpendicular diameters or whether necrosis developed de novo. Univariate and multivariate associations of baseline necrosis with overall survival (OS) and progression-free survival (PFS) were tested by log-rank test. Hazard ratios (HR) with 95% confidence interval were calculated by Cox model. Results: Imaging necrosis at baseline was detected in 191 patients (53.2%) and was associated with worse OS and PFS in univariate, but not in multivariate analysis. Baseline necrosis was predictive for OS in the lomustine-only group (HR 1.46, p = 0.018). At weeks 6 and 12 of treatment, increase of baseline necrosis and de novo necrosis were strongly associated with worse OS and PFS in univariate and multivariate analysis (PFS both p < 0.001, OS univariate p < 0.001, multivariate p = 0.0046). Conclusion: Increase of and new development of imaging necrosis during treatment is a negative prognostic factor for patients with progressive glioblastoma. These data call for consideration of integrating the assessment of imaging necrosis as a separate item into the MRI response assessment criteria.